Indole alkaloids from Vinca erecta type of sarpagine and ajmaline - Adizov, Shahobiddin; Tashkhodjaev, Bakhodir (European Journal of Chemistry, 2019)
The single crystal X-ray diffraction method established the absolute configuration of the Vinca erecta indole alkaloids of the akuammidine sarpagine type (3S, 5S, 15R, 16R) and its o-acyl derivative, as well as the type of ajmaline, quebrachidine (2S, 3S, 5S, 7R, 15S, 16R, 17S) and majoridine (2R, 3S, 5S, 7R, 15R, 16S, 17R). Crystal data for C21H24N2O3 (1): orthorhombic, space group P212121 (no. 19), a = 6.3949(5) Å, b = 13.5009(10) Å, c = 22.461(3) Å, Z = 4, 7694 reflections measured (7.64° ≤ 2Θ ≤ 152.294°), 3813 unique (Rint = 0.0798) which were used in all calculations. The final R1 was 0.0680 (I > 2σ(I)) and wR2 was 0.1650 (all data). Crystal data for C23H26N2O4 (2): orthorhombic, space group P212121 (no. 19), a = 9.9730(13) Å, b = 10.2090(10) Å, c = 20.409(3) Å, Z = 4, 7959 reflections measured (8.666° ≤ 2Θ ≤ 151.998°), 4212 unique (Rint = 0.0386) which were used in all calculations. The final R1 was 0.0477 (I > 2σ(I)) and wR2 was 0.1171 (all data). Crystal data for C42H48N4O6 (3): monoclinic, space group P21 (no. 4), a = 8.9320(10) Å, b = 21.515(5) Å, c = 9.5420(10) Å, β = 97.103(10)°, Z = 2, 16677 reflections measured (9.34° ≤ 2Θ ≤ 151.836°), 7393 unique (Rint = 0.0278) which were used in all calculations. The final R1 was 0.0366 (I > 2σ(I)) and wR2 was 0.1037 (all data). Crystal data for C23H28N2O3 (4): orthorhombic, space group P212121 (no. 19), a = 10.636(2) Å, b = 11.208(12) Å, c = 16.725(13) Å, Z = 4, 1650 reflections measured (9.498° ≤ 2Θ ≤ 119.97°), 1650 unique (Rint = 0.0436) which were used in all calculations. The final R1 was 0.0608 (I > 2σ(I)) and wR2 was 0.1720 (all data). In alkaloids such as sarpagine and ajmaline exo, the substituents of alkaloids do not lead to conformational changes of a stable polycyclic framework. In the series of sarpagine, alkaloids form mono-salts in the tetrahedral nitrogen N4, and in indolines of the ajmaline type, the tetrahedral hybridization of the N1 and N4 atoms favors the formation of disols. In V. erecta alkaloids, the exomethylene fragment (C18-C19=C20-C21) of the polycyclic backbone always takes on the E-state.